Intra and inter-rater reliability of web plot digitizer software in quantifying head posture angles - Yughdtheswari, Muniandy; Devinder Kaur Ajit, Singh; Suresh, Mani; Omar, Baharudin (Diva Enterprises Pvt Ltd, 2019)
Background